AZD7545, a novel inhibitor of pyruvate dehydrogenase kinase 2 (PDHK2), activates pyruvate dehydrogenase in vivo and improves blood glucose control in obese (fa/fa) Zucker rats. (1st December 2003) - Mayers, R.M.; Butlin, R.J.; Kilgour, E.; Leighton, B.; Martin, D.; Myatt, J.; Orme, J.P.; Holloway, B.R.
Abstract : PDH (pyruvate dehydrogenase) is a key enzyme controlling the rate of glucose oxidation, and the availability of gluconeogenic precursors. Activation of PDH in skeletal muscle and liver may increase glucose uptake and reduce glucose production. This study describes the properties of AZD7545, a novel, small-molecule inhibitor of PDHK (PDH kinase). In the presence of PDHK2, AZD7545 increased PDH activity with an EC50 value of 5.2 nM. In rat hepatocytes, the rate of pyruvate oxidation was stimulated 2-fold (EC50 105 nM). A single dose of AZD7545 to Wistar rats increased the proportion of liver PDH in its active, dephosphorylated form in a dose-related manner from 24.7 to 70.3% at 30 mg/kg; and in skeletal muscle from 21.1 to 53.3%. A single dose of 10 mg/kg also significantly elevated muscle PDH activity in obese Zucker ( fa / fa ) rats. Obese, insulin-resistant, Zucker rats show elevated postprandial glucose levels compared with their lean counterparts (8.7 versus 6.1 mM at 12 weeks old). AZD7545 (10 mg/kg) twice daily for 7 days markedly improved the 24-h glucose profile, by eliminating the postprandial elevation in blood glucose. These results suggest that PDHK inhibitors may be beneficial agents for improving glucose control in the treatment of type 2 diabetes.